Analisis PDRB 34 Provinsi di Indonesia Pada Masa Pemerintahan Presiden Joko Widodo - Ghaly Rizquillah Ahrizal (Jurnal Ilmu Ekonomi, 2022)
This study is intended to analyze the direct influence of education, labor, information and communication technology development index (ICT-DI), and domestic investment (DI) on the gross regional domestic product (GRDP) of 34 provinces in Indonesia during the government period. President Joko Widodo. This study uses secondary data in the form of panel data, 2015-2020, using the variables of average length of school, working population, information and communication technology development index (ICT-DI), and domestic investment (DI). The analytical method used is Ordinary Least Square (OLS). The results showed that education and manpower had a significant effect on the GRDP of 34 provinces in Indonesia, while the ICT development index and DI did not significantly affect the GRDP of 34 provinces in Indonesia. For this reason, the government should be able to intensify the development of communication infrastructure and provide various trainings, especially for residents in archipelagic provinces, so that the value of ICT-DI can be increased. and also the government to get domestic investment as much as possible can be maximized again because, high and stable DI can help Indonesia in economic development.